Phrasal Verbs Found In the Movie “Finding Dory” and Their Translations Into Indonesian - Dewi Satya Utami, Ni Made (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p33, 2018)
The objectives of this research are to analyze the types of translation procedures of phrasal verb in the movie Finding Dory subtitle by Andrew Staton and describe the skewed information of phrasal verb found in the target language. The type of this research belongs to  descriptive qualitative research. The data of the research are sentences containing phrasal verbs in the movie subtitle entitled Finding Dory. The method of collecting data was documentation method and note taking technique and the data were analyzed by comparing phrasal verbs between the source language and target language in the Movie Finding Dory subtitle. The result of this study shows that the types of translation procedures mostly used are transposition and modulation. There is skewed information found in the translation of phrasal verbs. From the result of the study, it can be concluded that there are differences in terms of structural formation of words between the source and the target language, different perspectives between two languages, and in translating between SL and TL resulting in the skewed information which is not the exact equivalent of the SL. It also causes distortion in the message.